IMPLEMENTASI PENGEMBANGAN MEDIA WAYANG KERTON PADA TEMA KEGIATAN SEHARI-HARI - Reffiane, Fine; Mazidati, Irvina (Mimbar Sekolah Dasar, 2016)
Saturation of the students to the learning effect on student learning outcomes is unsatisfactory. Teacher as facilitator in learning process needs a media that can enhance students' interest in participating in learning activities, one of which is the puppet media Kerton (paperboard). It is intended that the learning process can be effective, innovative, creative, and imaginative. The type of this research is research and development (RD). Subjects of the research in this study were 25 students of class. The result of the development media is puppets Kerton (paperboard). Media validation results at the first obtained 65% and the second media validation obtained percentage of 95%. The results of the validation expert guidance material on the first obtained 66.6% with the results of expert validation and guidance material on the second obtained 90.6%. Products that have been validated will be tested on all students. Average of students’ pretest score is 71.70, while the average of students’ post test score is 85.03. Results N gain is 0.52, which showed moderate criteria. It shows the puppet media Kerton (paperboard) fit for use as a media of learning because it can improve student learning outcomes.Keywords: media, puppets, cardboard.